Immune changes beyond Th2 pathways during rapid multifood immunotherapy enabled with omalizumab. Issue 9 (29th May 2021) - Manohar, Monali; Dunham, Diane; Gupta, Sheena; Yan, Zheng; Zhang, Wenming; Minnicozzi, Samantha; Kirkey, Matthew; Bunning, Bryan; Roy Chowdhury, Roshni; Galli, Stephen J.; Boyd, Scott D.; Kost, Laurie Elizabeth; et al.
Abstract: Background: Multifood oral immunotherapy (mOIT) with adjunctive anti‐IgE (omalizumab, XOLAIR ® ) treatment affords safe, effective, and rapid desensitization to multiple foods, although the specific immune mechanisms mediating this desensitization remain to be fully elucidated. Methods: Participants in our phase 2 mOIT trial (NCT02643862) received omalizumab from baseline to week 16 and mOIT from week 8 to week 36. We compared the immune profile of PBMCs and plasma taken at baseline, week 8, and week 36 using high‐dimensional mass cytometry, component‐resolved diagnostics, the indirect basophil activation test, and Luminex. Results: We found (i) decreased frequency of IL‐4 + peanut‐reactive CD4 + T cells and a marked downregulation of GPR15 expression and CXCR3 frequency among γδ and CD8 + T‐cell subsets at week 8 during the initial, omalizumab‐alone induction phase; (ii) significant upregulation of the skin‐homing receptor CCR4 in peanut‐reactive CD4 + T and Th2 effector memory (EM) cells and of cutaneous lymphocyte‐associated antigen (CLA) in peanut‐reactive CD8 + T and CD8 + EM cells; (iii) downregulation of CD86 expression among antigen‐presenting cell subsets; and (iv) reduction in pro‐inflammatory cytokines, notably IL‐17, at week 36 post‐OIT. We also observed significant attenuation of the Th2 phenotype post‐OIT, defined by downregulation of IL‐4 peanut‐reactive T cells and OX40 in Th2EM cells, increased allergen component‐specific IgG4/IgE ratio, and decreased allergen‐driven activation of indirectly sensitized basophils. Conclusions: This exploratory study provides novel comprehensive insight into the immune underpinnings of desensitization through omalizumab‐facilitated mOIT. Moreover, this study provides encouraging results to support the complex immune changes that can be induced by OIT. Abstract : Omalizumab (anti‐IgE) treatment alone for 8 weeks: decreased GPR15 in naïve γδ and effector memory Th2, and decreased frequency of IL‐4 + pr CD4 + cells. Desensitization at week 36 post‐omalizumab adjunctive multifood OIT: decrease in Th2 features: IL‐4, OX40, and basophil activation, and increase in IgG4/IgE. Also at week 36: increase in skin‐homing receptors CCR4 and CLA, decreased CD86 on antigen‐presenting cells, and decreased IL‐17 and pro‐inflammatory cytokines. Abbreviations: CCR4, chemokine receptor 4; CLA, cutaneous lymphocyte‐associated antigen; GPR15, G protein‐coupled receptor 15; OIT, oral immunotherapy; pr, peanut‐reactive (CD69 + CD40L + ).